1992
DOI: 10.1073/pnas.89.18.8789
|View full text |Cite
|
Sign up to set email alerts
|

A 2-O-methylfucose moiety is present in the lipo-oligosaccharide nodulation signal of Bradyrhizobium japonicum.

Abstract: A 2-0-methylfucose moiety is present in the lipo-oligosaccharide ABSTRACTBradyrhizobiumjaponicum is a soil bacterium that forms nitrogen-fixing nodules on the roots of the agronomically important legume soybean. Microscopic observation of plant roots showed that butanol extract of B. japonicum strain USDA110 cultures induced for nod gene expression elicited root hair deformation, an early event in the modulation process. The metabolite produced by B. japonicum responsible for root hair deformation activity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0
3

Year Published

1994
1994
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(110 citation statements)
references
References 17 publications
4
103
0
3
Order By: Relevance
“…Although most of these compounds represent variations on a common theme that also appears in two other soybean symbionts, Bradyrhizobium japonicum [14] and B. elkanii [15], strain USDA191 and mutant 257DH4 appear to be unique in their ability to synthesize a pentamer with a glucose inserted into the center of the oligochitin backbone. Although a pentameric LCO with mannose at its reducing terminus was recently identified in R. tropici [16], R. fredii synthesizes the first example of an LCO with a neutral sugar sandwiched between N-acetyl-D-glucosamine residues.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of these compounds represent variations on a common theme that also appears in two other soybean symbionts, Bradyrhizobium japonicum [14] and B. elkanii [15], strain USDA191 and mutant 257DH4 appear to be unique in their ability to synthesize a pentamer with a glucose inserted into the center of the oligochitin backbone. Although a pentameric LCO with mannose at its reducing terminus was recently identified in R. tropici [16], R. fredii synthesizes the first example of an LCO with a neutral sugar sandwiched between N-acetyl-D-glucosamine residues.…”
Section: Discussionmentioning
confidence: 99%
“…The first deformation occurs within 1 h after Nod factor application, whereas an increased cytoplasmic streaming occurs within 30 min (data not shown). In most other studies, root hair deformation was first scored several days after Nod factor application (Lerouge et al, 1990;Spaink et al, 1991;Price et al, 1992;Sanjuan et al, 1992;Schultze et al, 1992;Mergaert et al, 1993). Therefore, it is not clear whether such studies provide an accurate comparison of the abilities of different Nod factors to induce deformation.…”
Section: Discussionmentioning
confidence: 99%
“…105, 1994 deformation was scored 3 h after inoculation with R. leguminosarum bv trifolii and these deformed root hairs were present in a zone located 2 to 5 mm from the tip (Bhuvaneswari and Solheim, 1985). However, in a11 but one (Firmin et al, 1993) of the studies to determine Nod factor activity, root hair deformation was examined severa1 days after addition of Nod factor (Lerouge et al, 1990;Spaink et al, 1991;Price et al, 1992;Sanjuan et al, 1992;Schultze et al, 1992;Mergaert et al, 1993).…”
Section: Research (Nwo)mentioning
confidence: 99%
“…Spaink et al (1995) have recently suggested that the recognition of NOD factors by the host legume could be related to the different hydrophobicities exhibited by fatty acids present in NOD factor structure, thus opening the question if the chitin unit from NOD factors plays same role in the recognition process. Presently there are only a few available structures of NOD factors produced by symbiotic bacteria, although a new NOD factor showing an additional O-metyl-fucoside moiety in its structure was reported (Sanjuan et al, 1992;Cohn et al, 1998). Many others could be isolated and their structures established, especially in bacteria which interact with legume plants which do not express glucose/mannose lectins and the actual interaction between lectin and NOD factor (if possible) should be evaluated.…”
Section: Bauhinia Purpurea Galnacmentioning
confidence: 99%